2014
DOI: 10.1007/s00134-014-3339-z
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of an intervention to relieve thirst and dry mouth in intensive care unit patients

Abstract: Purpose To test an intervention bundle for thirst intensity, thirst distress, and dry mouth, which are among the most pervasive, intense, distressful, unrecognized, and under-treated symptoms in ICU patients, but for which data-based interventions are lacking. Methods Single-blinded, randomized clinical trial in three ICUs in a tertiary medical center in urban California. 252 cognitively intact patients reporting thirst intensity (TI) and/or thirst distress (TD) scores ≥ 3 on 0–10 numeric rating scales (NRS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
1
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 35 publications
6
101
1
11
Order By: Relevance
“…It should be known that some of these factors can be changed or reduced. Puntillo et al (17) reported that some stress factors in the ICU are subjective and can be modified. They stated that thirst, which was ranked 1st among stress factors in the ICU, can be reduced with simple and inexpensive methods such as placing wet gauze on the lips and using cold water sprays.…”
Section: Discussionmentioning
confidence: 99%
“…It should be known that some of these factors can be changed or reduced. Puntillo et al (17) reported that some stress factors in the ICU are subjective and can be modified. They stated that thirst, which was ranked 1st among stress factors in the ICU, can be reduced with simple and inexpensive methods such as placing wet gauze on the lips and using cold water sprays.…”
Section: Discussionmentioning
confidence: 99%
“…A temperatura fria conferida pelo gelo estimula receptores orofaríngeos, denominados Transient Receptor Potential Melastatin 8 (TRPM8), presentes tanto na pele quanto na cavidade oral. Esses receptores são sensíveis a baixas temperaturas e a substâncias mentoladas e derivadas do eucalipto (13,20) , capazes de produzir uma agradável sensação de prazer e conforto, levando à saciedade com uma ingestão de menor volume em comparação com a água gelada, diminuindo ainda mais os riscos para o paciente (3) . Esses avanços no manejo da sede perioperatória podem significar uma diminuição desse desconforto para o paciente em recuperação anestésica, desde que adotados na prática clínica.…”
Section: Encontrando Dificuldades Para a Avaliação E Manejo Da Sedeunclassified
“…Dentre as complicações que podem acometer o paciente no POI, a sede apresenta alta prevalência (75%) (2) e interfere de forma prejudicial na recuperação pós-anestésica. Relatos de pacientes indicam que a sede causa grande distresse e, consequentemente, acarreta sentimentos negativos, como ansiedade e irritabilidade, com alusões a sentimentos de desespero e até pensamentos de morte (3) . Ainda que, no POI, a sede tenha alta prevalência e intensidade e represente distresse, paradoxalmente ela permanece subidentificada e submensurada, e as medidas de alívio na prática clínica não estão padronizadas (1,5) .…”
Section: Introductionunclassified
“…Puntillo et al 69 completed an RCT of an intervention to decrease thirst intensity and distress.This study used standardized 1 to 10 scales to assess thirst intensity ("How intense is your thirst? "; 0 = no thirst to 10 = worst possible thirst) and thirst distress ("How distressing [or bothersome] is your thirst?…”
Section: Thirstmentioning
confidence: 99%